Clinical and imaging characteristics of encapsulated papillary carcinoma: a comparative analysis with intraductal papilloma - Zhi-long Liu; Qian Zhang; Qin Lu; Chao Zhang; Juan Chen; Yan-yan Dong; Li-ping Liu (World Journal of Surgical Oncology)
Abstract Objective Encapsulated papillary carcinoma (EPC) exhibits clinical and imaging characteristics that resemble those of the benign tumor intraductal papilloma (IDP). The differences between these two entities have not been extensively studied. The objective of this study is to evaluate and compare the clinical and imaging features of EPC and IDP. Methods A retrospective analysis was conducted using data from 36 patients diagnosed with EPC and 30 patients diagnosed with IDP at a single center between May 2016 and May 2023. Clinical parameters, including patient age and the presence of nipple discharge, as well as imaging parameters such as nodule size, shape, margins, aspect ratio, internal structure, calcifications, posterior acoustic enhancement, blood flow signals, and Breast Imaging Reporting and Data System (BI-RADS) classification, were compared between the two groups. Results The mean age of patients with EPC was significantly higher than that of those with IDP (60.39 years vs. 49.27 years, p < 0.01). EPC nodules were larger in size (3.00 ± 2.17 cm vs. 2.11 ± 0.85 cm) and more frequently exhibited a cystic-solid composition (61.11% vs. 36.67%, p < 0.05). Posterior acoustic enhancement was observed in 72.22% of EPCs compared to 40.00% of IDPs (p < 0.01). Additionally, EPCs were associated with a higher incidence of abundant blood flow signals (grade ≥ 2) than IDPs (63.89% vs. 36.67%, p < 0.05). No significant differences were noted in terms of nodule morphology, margins, or BI-RADS classification. Mammographic features, including calcifications, were comparable between the two groups. Conclusion This study presents the imaging characteristics of EPC and identifies potential clinical and imaging differences between EPC and IDP. These findings support clinicians in distinguishing EPC from IDP more effectively.